Successful Ultrasound-Guided Femoral Nerve Blockade and Catheterization in a Patient with Von Willebrand Disease - Youmna E. DiStefano; Michael D. Lazar (Case Reports in Anesthesiology)
Peripheral nerve blockade (PNB) is superior to neuraxial anesthesia and/or opioid therapy for perioperative analgesia in total knee replacement (TKR). Evidence on the safety of PNB in patients with coagulopathy is lacking. We describe the first documented account of continuous femoral PNB for perioperative analgesia in a patient with Von Willebrand Disease (vWD). Given her history of opioid tolerance and after an informative discussion, a continuous femoral PNB was planned for in this 34-year-old female undergoing TKR. A Humate-P intravenous infusion was started and the patient was positioned supinely. Using sterile technique with ultrasound guidance, a Contiplex 18 Gauge Tuohy needle was advanced in plane through the fascia iliaca towards the femoral nerve. A nerve catheter was threaded through the needle and secured without complications. Postoperatively, a levobupivacaine femoral catheter infusion was maintained, and twice daily Humate-P intravenous infusions were administered for 48 hours; enoxaparin thromboprophylaxis was initiated thereafter. The patient was discharged uneventfully on postoperative day 4. Given documentation of delayed, unheralded bleeding from PNB in coagulopathic patients, we recommend individualized PNB in vWD patients. Multidisciplinary team involvement is required to guide factor supplementation and thromboprophylaxis, as is close follow-up to elicit signs of bleeding throughout the delayed postoperative period.